Does the face mask increase the impact of rapid maxillary expansion on sagittal airway dimensions? - Muhsin Çifter; Özge Ekmen; Asuman Deniz Gümrü Çelikel; Beyza Tağrikulu; Elif Erbay (European Oral Research)
Purpose: Airway dimensions associated with the transversal and sagittal position of the maxilla are affected by orthodontic treatment. The objective of this study was to compare the effects of rapid maxillary expansion (RME) and RME followed by face mask (FM) therapies on the airway space and investigate whether application of the FM increases the short-term and long- term impact of RME on sagittal airway dimensions. Materials and Methods: A total of 26 patients were divided into two groups. Group I included 14 adolescents treated with RME (3 males, 11 females; mean age: 12.2 11 ± 2.1 years), and Group II included 12 adolescents treated with RME followed by FM therapy (7 males, 5 females; mean age: 11.6 ± 1.3 years). Sagittal and vertical skeletal measurements, as well as ten linear cross-sectional airway measurements, were calculated from pretreatment, posttreatment, and postretention cephalometric radiographs. Results: RME followed by FM resulted in a significant increase in the SNA angle, ANB angle, and Wits parameter by the forward movement of the maxillary bone. A significant increase in the vertical dimensions was also observed. Regarding the airway measurements in both groups, significant oropharyngeal increases were revealed, and these were maintained in the follow-up period. However, there were no other significant differences in the short-term and long-term results obtained for Groups I and II. Conclusion: The dimensions of the airway were significantly affected by both therapies. However, no additional effect of FM was observed.